Mekanisme Fiktif Positif, Pengaturan Tata Ruang, Dan Hubungan Pusat-Daerah Dalam Kerangka UU Cipta Kerja: Tawaran Rekomendasi Kebijakan - Maria Dika Puspita Sari; Antonius Galih Prasetyo (Kybernan: Jurnal Studi Kepemerintahan, 2022)
The birth of the Job Creation Law supports the ease and certainty of doing business in Indonesia. In general, this law marks a change in the paradigm of business licensing in Indonesia, from being license-based to risk-based. One form of accelerating the licensing process is through positive fictitious mechanisms, one of which is contained in the licensing process related to the Conformity of Spatial Utilization Activities (KKPR) with Regional Spatial Detail Plans (RDTR). This new regulation has the potential to be ineffective because only a small number of regions in Indonesia have RDTR integrated into the RBA OSS system. In addition, the position of authority for spatial planning is mostly in the Central Government, even though this spatial planning issue is site specific and the Regional Government also has an interest in the utilization and control of space for regional development efforts. Several alternative policies to anticipate this, namely (1) accelerating the preparation of RDTR for strategic regions, (2) accelerating RDTR in all regions, and (3) encouraging collaboration between the Central Government and Regional Governments in terms of KKPR assessment and supervision. Based on the analysis of the effectiveness and resources needed to implement the three policy alternatives, the policy recommendations focus on the third alternative.